Future of Russia: Macroeconomic Scenarios in the Global Context - Elena Abramova; Alexander Apokin; Dmitry Belousov; Kirill Mikhailenko; Elena Penukhina; Alexander Frolov (Foresight and STI Governance, 2013)
The recent global crisis has “devalued” many pre-crisis forecasts and strategies, including those in Russia. This fostered the redesigning of science, technology and innovation (STI) policy frameworks to adjust the scope and priorities of STI funding and to elaborate a new set of long-term strategic planning documents, in particular, to revise the Russian Long-Term S&T Foresight. Since S&T and broader socio-economic processes are closely interrelated, the new macroeconomic forecasting is a key building block for updating Russian Long-Term S&T Foresight; it is carried out by the Center for Macroeconomic Analysis and Short-Term Forecasting (CMASF). The article presents interim results, namely, a set of possible scenarios of global development and their projections for Russia.